Psychosocial Factors and Burnout Syndrome in Academics of a Public University from Mexico - Villamar Sánchez, Daniela (2019)
The objective of the study was to identify the relationship between psychosocial factors of academic work and Burnout Syndrome in a public university in Mexico. In a sample of 247 academics from a public university in Mexico, an online battery was applied that was made up of an adaptation of the questionnaire Psychosocial Factors of Academic Work (FPSIS), the Questionnaire for the Evaluation of Burning Syndrome by Work for Educational Professionals (CESQT-PE) and a section on sociodemographics The high and/or critical prevalence of Burnout dimensions was around 30% at the same time as more than 90% showed high levels of illusion at work. Multivariate linear regression models showed a statistically significant relationship between all psychosocial factors and most Burnout dimensions independent of sex, age or marital status, reaching explained variances between 16% and 43%. The most reliable predictors were "social and organizational problems" and "problems with students", which also had higher prevalence (40.9% and 34.8% respectively). Negative dimensions of burnout and Illusion for work seem to coexist to some extent. The psychosocial factors found are clearly linked to the new higher education policies. It is recommended to implement actions at the institutional level that contribute to improving working conditions and well-being, as well as preventive programs to reduce work stress and improve the quality of life of academics.